2012
DOI: 10.1177/1045159512452844
|View full text |Cite
|
Sign up to set email alerts
|

Envisioning an Adult Learning Graduate Program for the Early 21st Century

Abstract: The rapid pace of social and technological change in the early 21st century leaves many adults scrambling to meet the complexities that characterize their daily lives. Adult learners are faced with multiple, often competing, demands from work, education, family, and leisure, which requires adult education graduate programs to carefully consider how best to meet these changing needs of today’s students. Using a developmental action inquiry approach, the authors collected data using multiple rounds of mutual inq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Knowles (1978) says that in regards to learning, we become adults when we accept responsibility for our learning and are self-directed. Therefore, in that RN-to-BS and graduate nursing students can be categorized as adult learners, it is important that nursing educators understand adult learners and what it means for them to be online learners (Anderson, 2008;Dzubinski et al, 2012;Hussain, 2013).…”
Section: Andragogical Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Knowles (1978) says that in regards to learning, we become adults when we accept responsibility for our learning and are self-directed. Therefore, in that RN-to-BS and graduate nursing students can be categorized as adult learners, it is important that nursing educators understand adult learners and what it means for them to be online learners (Anderson, 2008;Dzubinski et al, 2012;Hussain, 2013).…”
Section: Andragogical Theorymentioning
confidence: 99%
“…For example, online students have been shown to employ broader reading strategies and adapt more easily to instructional strategies that focus on acquisition of lifelong learning skills (Dykman & Davis, 2008;National Survey of Student Engagement, 2012). Online teaching strategies are key in enabling students to learn how to locate information on their own to foster self-directed learning and continue providing professional skills throughout their careers (Anderson, 2008;Dzubinski, Hentz, Davis, & Nicolaides, 2012;Hussain, 2013).…”
mentioning
confidence: 99%
“…Different group of stakeholders in adult education were asked about the role of their education institutions in assisting adults, organizations and society meet the demands of 21 st century life. This work revealed that adult education has to include and design dynamic graduate programs which could support the cultivation of critical and timely reflection, create online learning environments and center the relationship between adult learning and development capacity due to prepare adult education facilitators who stand surely in the face of complexity (Dzubinski, Hentz, Davis & Nicolaides, 2012) Curtis Boehmer (2011) studied the impact of technology on the cognitive learning of the children. The researcher believes that video game has been an effective element in education and has now been accepted to assist students to think, find solution to problems and overcome difficulties.…”
Section: Program Effectivenessmentioning
confidence: 99%
“…st century is defined as a century of developing knowledge based digital information technologies and economics (Dzubinski et al, 2012;Lai, 2011). Things have started to appear differently as we have entered a new era.…”
mentioning
confidence: 99%
“…Today, the typical demands of adulthood are now coupled with a new norm of ever‐growing complexity, instability, and ambiguity. These realities have become taken for granted and much discussed assumptions in the fields of adult learning and organizational studies where practitioners and scholars have focused their attention on helping adults and organizations navigate this new landscape (Dzubinski, Hentz, Davis, & Nicolaides, ; Merriam, Caffarella, & Baumgartner, ). A paradox of our contemporary organizations and society is that we are accumulating new knowledge at an ever‐increasing rate, while at the same time we are confronted with potential disasters stemming from the unanticipated, nonlinear consequences of this accumulating body of knowledge.…”
mentioning
confidence: 99%